Determinants of repayment performance in credit groups: the role of program design, intra-group risk pooling, and social cohesion in Madagascar - Zeller, Manfred (International Food Policy Research Institute, 1996)
Group lending has received much attention in recent years because of its perceived potential in providing financial services to poor households that lack traditional collateral. The analysis in this paper focuses on the effects of program design, community and group characteristics on the repayment performance of groups, using a data set on groups from six different lending programs in Madagascar. The results show that socially cohesive groups pool risks by diversifying the members’ asset portfolio so that their repayment performance is improved even in communities with high-risk exposure.